Brushite-based calcium phosphate cement with multichannel hydroxyapatite granule loading for improved bone regeneration. (January 2016) - Sarkar, Swapan Kumar; Lee, Byung Yeol; Padalhin, Andrew Reyas; Sarker, Avik; Carpena, Nathaniel; Kim, Boram; Paul, Kallyanshish; Choi, Hwan Jun; Bae, Sang-Ho; Lee, Byong Taek
In this work, we report brushite-based calcium phosphate cement (CPC) system to enhance the in vivo biodegradation and tissue in-growth by incorporation of micro-channeled hydroxyapatite (HAp) granule and silicon and sodium addition in calcium phosphate precursor powder. Sodium- and silicon-rich calcium phosphate powder with predominantly tri calcium phosphate (TCP) phase was synthesized by an inexpensive wet chemical route to react with mono calcium phosphate monohydrate (MCPM) for making the CPC. TCP nanopowder also served as a packing filler and moderator of the reaction kinetics of the setting mechanism. Strong sintered cylindrical HAp granules were prepared by fibrous monolithic (FM) process, which is 800 µm in diameter and have seven micro-channels. Acid sodium pyrophosphate and sodium citrate solution was used as the liquid component which acted as a homogenizer and setting time retarder. The granules accelerated the degradation of the brushite cement matrix as well as improved the bone tissue in-growth by permitting an easy access to the interior of the CPC through the micro-channels. The addition of micro-channeled granule in the CPC introduced porosity without sacrificing much of its compressive strength. In vivo investigation by creating a critical size defect in the femur head of a rabbit model for 1 and 2 months showed excellent bone in-growth through the micro-channels. The granules enhanced the implant degradation behavior and bone regeneration in the implanted area was significantly improved after two months of implantation.